African Economies in the Shadow of China: Effects of Bilateral Trade Structure on Economic Growth in Africa. Issue 1 (February 2020) - Maswana, Jean-Claude
This study aimed at assessing the effects of bilateral trade intensity by export categories in the China–Africa trade links on economic growth in Africa, by using a production function approach in a panel system GMM estimator. The findings suggest that conditional on the level of the logistics index and China's FDI to Africa, economic growth tends to be greater in countries with higher index of trade intensity in manufactured exports to China. Another noticeable finding is that the potential contribution of manufactured exports to economic growth is higher than that of primary exports; African countries are constrained in their trade expansion with China by low-logistics quality. Surprisingly, the current logistics infrastructure, as low quality as they are, remain somehow adequate for primary commodity exports to China. JEL Codes: F14, F43, O19, O47, O55